2022
DOI: 10.3233/atde220559
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review of Industry 4.0 Implementation Frameworks Focusing on Applicability in Manufacturing SMEs

Abstract: Industry 4.0 (I4.0) is not an exceedingly new concept. Since the term was coined in Germany in 2011 it has come to encompass many enabling technologies around the digitalisation of manufacturing processes growing further into the service industry and beyond. The need for businesses to begin to explore these options to reap the benefits of I4.0 is growing and while many larger organisations are maturing in their adoption many SMEs are not. This paper conducts a systematic literature review (SLR) of the tools av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Frameworks can also be of strategic type -the ones that are related to designing or pursuing a certain organizational strategy, or procedural type -the ones that are related to the governance of certain activities. Some authors include the maturity models in the group of frameworks for the implementation of DT and I4.0 (Denning & Liyanage, 2022). This question was previously extensively researched in (Argilovski et al, 2022).…”
Section: Dt and I40 Framework Literature Reviewmentioning
confidence: 99%
“…Frameworks can also be of strategic type -the ones that are related to designing or pursuing a certain organizational strategy, or procedural type -the ones that are related to the governance of certain activities. Some authors include the maturity models in the group of frameworks for the implementation of DT and I4.0 (Denning & Liyanage, 2022). This question was previously extensively researched in (Argilovski et al, 2022).…”
Section: Dt and I40 Framework Literature Reviewmentioning
confidence: 99%
“…Another focus in another framework is about on a sociotechnical perspective that analyzed the relationship between technology implementation and organizational changes [23]. Meanwhile, another framework focuses on the training and re-skilling process to build a strong workforce for Industry 4.0 implementation [24] and a study that examines several existing frameworks to see how a framework can be flexible and sustainable to help SMEs implement Industry 4.0, but this research is still at the stage of comparing different frameworks [25]. These studies have revealed clear knowledge gaps in how to effectively and sustainably apply Industry 4.0 in manufacturing SMEs, highlighting the need for a holistic framework to help SMEs overcome the challenges they face in adopting Industry 4.0.…”
Section: Introductionmentioning
confidence: 99%
“…Az elmúlt években számos modell próbálta megragadni a legfontosabb előfeltételeket (Lichtblau és szerzőtársai [2015], Nick és szerzőtársai [2021], Santos-Martinho [2020]), de valódi áttörés nem történt. A lehetséges okok között szerepel, hogy hiányzik egy olyan ipar 4.0 felkészültségi modell, amely valóban a kis-és középvállalatokra modellezné a problémát (Denning-Liyanage [2022], Mittal és szerzőtársai [2018]). Jelen munkánkban erre a kutatási résre összpontosítunk.…”
unclassified